We have to find the antiderivative of y=1/(x-1)(x+4)

First let's express y as partial fractions.

y = A / (x - 1) + B/(x + 4)

=> y=1/(x-1)(x+4) = A/(x - 1) + B/(x + 4)

=> Ax + 4A + Bx - B = 1

=> A + B...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the antiderivative of y=1/(x-1)(x+4)

First let's express y as partial fractions.

y = A / (x - 1) + B/(x + 4)

=> y=1/(x-1)(x+4) = A/(x - 1) + B/(x + 4)

=> Ax + 4A + Bx - B = 1

=> A + B = 0 and 4A - B = 1

Add the two,

5A = 1

A = 1/5

B = -1/5

y = 1/5(x - 1) - 1/5(x + 4)

Int [ y dy] = Int [ 1/5(x - 1) - 1/5(x + 4) dy]

=> (ln|x - 1| - ln|x + 4|)/5

=> ln[(x - 1)/(x + 4)]/5 + C

**The required derivative is ln[(x - 1)/(x + 4)]/5 + C**